Specific contribution of lamin A and lamin C in the development of laminopathies - Sylvius, Nicolas (2008)
Mutations in the lamin A/C gene are involved in multiple human disorders for which the pathophysiological mechanisms are partially understood. Conflicting results prevail regarding the organization of lamin A and C mutants within the nuclear envelope (NE) and on the interactions of each lamin to its counterpart. We over-expressed various lamin A and C mutants both independently and together in COS7 cells. When expressed alone, lamin A with cardiac/muscular disorder mutations forms abnormal aggregates inside the NE and not inside the nucleoplasm. Conversely, the equivalent lamin C organizes as intranucleoplasmic aggregates that never connect to the NE as opposed to wild type lamin C. Interestingly, the lamin C molecules present within these aggregates exhibit an abnormal increased mobility. When co-expressed, the complex formed by lamin A/C aggregates in the NE. Lamin A and C mutants for lipodystrophy behave similarly to the wild type. These findings reveal that lamins A and C may be differentially affected depending on the mutation. This results in multiple possible physiological consequences which likely contribute in the phenotypic variability of laminopathies. The inability of lamin C mutants to join the nuclear rim in the absence of lamin A is a potential pathophysiological mechanism for laminopathies.